2017
DOI: 10.1074/jbc.m116.757500
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-specific SoxR-mediated Regulation of an Endoribonuclease Protects Non-enteric Bacteria from Redox-active Compounds

Abstract: Edited by F. Peter GuengerichBacteria use redox-sensitive transcription factors to coordinate responses to redox stress. The [2Fe-2S] cluster-containing transcription factor SoxR is particularly tuned to protect cells against redox-active compounds (RACs). In enteric bacteria, SoxR is paired with a second transcription factor, SoxS, that activates downstream effectors. However, SoxS is absent in nonenteric bacteria, raising questions as to how SoxR functions. Here, we first show that SoxR of Acinetobacter olei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Previously, our lab has shown that GS-participating genes in a soil-borne bacterium, A . oleivorans DR1, are upregulated upon exposure to ampicillin, paraquat (PQ), phenazine methosulfate (PMS), hexadecane (Hex), and triacontane (TRI)-treated condition 1418 . Examination of an aceA -deficient strain in triaconatane (C30 alkane)-containing minimal salt basal (MSB) media showed retarded growth with a long lag phase in contrast to that observed for the parent strain, and the susceptibility of the ICL-lacking mutant to H 2 O 2 was considerably increased 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, our lab has shown that GS-participating genes in a soil-borne bacterium, A . oleivorans DR1, are upregulated upon exposure to ampicillin, paraquat (PQ), phenazine methosulfate (PMS), hexadecane (Hex), and triacontane (TRI)-treated condition 1418 . Examination of an aceA -deficient strain in triaconatane (C30 alkane)-containing minimal salt basal (MSB) media showed retarded growth with a long lag phase in contrast to that observed for the parent strain, and the susceptibility of the ICL-lacking mutant to H 2 O 2 was considerably increased 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In non-enteric bacteria, a different response mechanism occurs, in which SoxS is not present. SoxR directly activates, not only the expression of genes involved in antioxidant defense, but also up-regulates mono- and dioxygenases-encoding genes (Dietrich and Kiley, 2011; Kim et al, 2017). Accordingly, SoxR2 of A. aquatilis QD168 clustered with proteins from non-enteric bacteria and the soxS gene is not present in its genome.…”
Section: Discussionmentioning
confidence: 99%
“…For the leakproof and tightly regulated expression of each regulon, promoters of the target genes of each regulon need to differentiate distinctly. At the same time, the amino acid residues of regions 2.4, 3.0, and 4.2 of the RpoH, which are involved in the recognition of the Ϫ10, extended Ϫ10, and Ϫ35 promoter elements of the heat shock genes (14), also need to change accordingly so as to recognize their target promoters and to insulate each regulon from the other (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…The levels of ROS in the cell are monitored by two types of transcription regulators. In response to the elevated levels of ROS, DNA binding transcription regulators such as OxyR, SoxR, or OhrR activate oxidative stress-responsive genes by binding to their promoter upstream regions (14). OxyR is a global transcriptional regulator of the LysR family which helps in coping with H 2 O 2 -induced oxidative damage by inducing expression of several genes (15,16).…”
mentioning
confidence: 99%